Measuring the Capacity Utilization of Public District Hospitals in Tunisia: Using Dual Data Envelopment Analysis Approach - Chokri Arfa; Hervé Leleu; Mohamed Goaïed; Cornelis van Mosseveld (Kerman University of Medical Sciences, 2017)
Background Public district hospitals (PDHs) in Tunisia are not operating at full plant capacity and underutilize their operating budget. Methods Individual PDHs capacity utilization (CU) is measured for 2000 and 2010 using dual data envelopment analysis (DEA) approach with shadow prices input and output restrictions. The CU is estimated for 101 of 105 PDH in 2000 and 94 of 105 PDH in 2010. Results In average, unused capacity is estimated at 18% in 2010 vs. 13% in 2000. Of PDHs 26% underutilize their operating budget in 2010 vs. 21% in 2000. Conclusion Inadequate supply, health quality and the lack of operating budget should be tackled to reduce unmet user's needs and the bypassing of the PDHs and, thus to increase their CU. Social health insurance should be turned into a direct purchaser of curative and preventive care for the PDHs.